2000
DOI: 10.2118/66540-pa
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Accurate Prediction of Loading in Gas Wells Under Different Flowina Conditions

Abstract: Summary Several authors have introduced various mathematical equations to calculate the critical flow rate necessary to keep gas wells unloaded. The most widely used equation is that of Turner et al.1 However, Turner's equation required empirical adjustment with different ranges of data which made the application rather questionable. In this paper we present a new approach for calculating the critical flow rate necessary to keep gas wells unloaded. This approach still adopts Turner's basic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…As presented in Table 1, several investigators have suggested different modified expressions derived from Turner model. Turner et al, 1969 Created the widely accepted Turner equation Coleman et al, 1991 Suggested not to use the 20% correction factor for low pressure gas wells Nosseir et al, 2000 Considered influences from different flow regimes Li et al, 2002 Involved the droplets' shape Veeken et al, 2003 Defined the concept of Turner ratio Guo et al, 2006 Took the minimum required kinetic energy of gas flow into account Belfroid et al, 2008 Concerned with the effects due to wellbore inclination Sutton et al, 2010 Used more realistic PVT properties Zhou and Yuan, 2010 Included the liquid droplet concentration in gas wells Veeken et al, 2010 Designed a specific expression for offshore gas wells Luan and He, 2012 Comprised droplets rollover in the gas rising process…”
Section: Current Prediction Approachesmentioning
confidence: 99%
“…As presented in Table 1, several investigators have suggested different modified expressions derived from Turner model. Turner et al, 1969 Created the widely accepted Turner equation Coleman et al, 1991 Suggested not to use the 20% correction factor for low pressure gas wells Nosseir et al, 2000 Considered influences from different flow regimes Li et al, 2002 Involved the droplets' shape Veeken et al, 2003 Defined the concept of Turner ratio Guo et al, 2006 Took the minimum required kinetic energy of gas flow into account Belfroid et al, 2008 Concerned with the effects due to wellbore inclination Sutton et al, 2010 Used more realistic PVT properties Zhou and Yuan, 2010 Included the liquid droplet concentration in gas wells Veeken et al, 2010 Designed a specific expression for offshore gas wells Luan and He, 2012 Comprised droplets rollover in the gas rising process…”
Section: Current Prediction Approachesmentioning
confidence: 99%
“…Later, many researchers (Coleman et al 1991;Nosseir et al 2000;Liu et al 2006;Wang and Liu 2007;Peng 2010) proposed many new critical-flow-velocity-calculation models by modifying the Turner et al (1969) model. Coleman et al (1991) reported that the correction factor of 20% in that model is not enough for the gas wells with low reservoir pressure, and gave a new correction for the coefficient, which can obtain the desired results.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2001) derived the critical-flow-velocity model with the coefficient of 2.5, assuming that the droplets would become ellipsoid in shape under the condition of high-speed gas-flow rate, and the drag coefficient of the ellipsoid is approximately unity. Nosseir et al (2000) and Liu et al (2006) noted that the drag coefficient is strongly related to the Reynolds number, and it is 0.2 when the Reynolds number is larger than 2 Â 10 5 , and the critical liquid-loading rate within the Reynolds number ranging from 3 Â 10 5 to 5 Â 10 6 was provided with the coefficient of the model of 6.65, which is larger than 5.46 in the Turner et al (1969) model and 6.6 in the modified Turner et al (1969) model. Wang and Liu (2007) argued that the shape of the droplet is a ball cap, according to the knowledge of fluid mechanics, and derived the formula of critical flow velocity with the coefficient of 1.8 and made a correction factor of 25% for the coefficient in the formula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the results with field data and verified that it was necessary to apply an upward factor of 20% to insure a better match. After that, Coleman et al (1991) and Nosseir et al (2000) presented further research that suggested the factor should be higher or was not necessary. In addition, Belfroid et al (2008) improved Turner's equation so that this could consider the effects of inclination of the tubing.…”
Section: Introductionmentioning
confidence: 99%